Understanding international students beyond studentification: A new class of transnational urban consumers. The example of Erasmus students in Lisbon (Portugal) - Calvo, Daniel Malet (Urban studies (Edinburgh, Scotland), 2018)
For the last 10 years the city of Lisbon has been receiving an increasing number of international students, expanding considerably the supply of student accommodation. In spite of the resulting rise of a new and underdeveloped housing market directed to students, studentification is not exhibiting the usual concentration and segregation patterns of clustering across the city. On the contrary, the effects of student-related economic activities are spreading throughout Lisbon, overlapping with several urban transformations. An examination of international students’ lifestyles in Lisbon seems to demonstrate that diverse youth cultures of Erasmus students are colonising different districts and activities through diverse processes of belonging and distinction. Beyond the studentification literature (and its housing-supply centred perspective) it is necessary to recognise that international students become involved in broader urban processes such as the tourism industry, marginal gentrification or entrepreneurial creativity, thus becoming a new class of transnational urban consumers. 过去十年来，里斯本的国际学生持续增长，学生住房的供给大幅扩展。虽然一个面向学生的新 的、欠发展的住房市场随之兴起，学生化并未在全市展现出通常的群落聚集和区隔格局。相反，与学 生相关的经济活动效应在整个里斯本散播，与一些城市转型进程相重合。对里斯本国际学生生 活方式的考察似乎表明，伊拉斯谟学生的多元青年文化通过多样化的归属和区分过程，正在占 据不同的街区和活动。除学生化研宄文献（集中于住房供给的视角）外，有必要认识到，国际 学生己卷入更大范围的城市进程中，例如旅游业、边缘性绅士化或企业家式创造力，从而成为 一个新的跨国城市消费阶层。